EU Menu Austria: Food consumption data for Austrian adolescents, adults and pregnant women: Department of Nutritional Sciences, University of Vienna, Austria. Issue 12 (9th December 2019) - König, Jürgen; Hasenegger, Verena; Rust, Petra
Abstract : The food consumption data collection from adults was part of the Austrian Study on Nutrition and the Austria Nutrition Report 2017. In addition to food consumption data from adults, data from adolescents and from pregnant women were collected. The food consumption reported was part of the EU Menu Project and thus followed as far as possible the EFSA EU Menu Guidance and specifications in the contract. A nationally representative sample of the adult Austrian population aged 18 to 64 years (n=2250) was selected using a multistage stratified cluster sampling procedure. The subgroup of adolescents from 10 to 17 years (n=657) was selected from the national school register by random sampling of schools and random sampling of classes within the selected schools. For pregnant women (n=302) a convenience sampling was conducted, as no register for this group was available. Data on food consumption was collected by using a repeated 2x24 hour recall in form of a computer assisted personal and computer assisted telephone interview implemented with GloboDiet dietary recall software tool. A food propensity questionnaire consisting of 28items and asocio‐demographic questionnaire provided information on typical food intake and on socio‐economic status. Body weight and height from all participants were measured during the first face‐to‐face meeting by trained fieldworkers. The food consumption data was linked to the FoodEx2 classification system in order to be included in the EFSA Comprehensive European Food Consumption Database for risk assessment purposes on European level and for assessment of nutrient intake for national health policies.